Trading Partners and Output Growth in Ukraine - Żyra, Joanna; Kopych, Roman (Dochód krajów – partnerów handlowych i wzrost gospodarczy w Ukrainie, 2023)
This study aimed to empirically estimate the long-term and short-term relations between the output of trading partners and economic growth in Ukraine. With the use of quarterly data over the 2004-2019 period, it was found that an increase of output in the euro area resulted in the most substantial stimulating long-term effect on the level of GDP in Ukraine, followed by spillovers from output growth in Poland. There was no long-term effect of output in other major trading partners, such as other Central and Eastern European countries (Czechia, Hungary, Slovakia) and the former Soviet Union countries (Belarus, Kazakhstan, Russia). In the short run, the stimulating effect of foreign output was confirmed only for spillovers from the euro area. Among other results, there was a longterm contractionary effect of both exchange rate depreciation and liberalisation of the economic environment, as indicated by the Index of Economic Freedom from the Washington-based Heritage Foundation (both factors are neutral with respect to Ukraine’s output in the short run).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 4, s. 172-181
Keywords: output growth; foreign output spillovers; exchange rate; index of economic freedom; Ukraine; wzrost gospodarczy; efekt dochodu za granicą; kurs walutowy; indeks wolności gospodarczej; Ukraina